Management system of dangerous waste (dry batteries and batteries) at the Faculty of the Geological, Mining, Metallurgical and Geographical Engineering of the San Marcos National Major University - Canchari Silverio, Godelia (2010)
The management of solid dangerous wastes at the Faculty of the Geological, Mining, Metallurgical and Geographical Engineering of the San Marcos National Major University is the first step towards the integration of the environmental system of management at the campus, following standards of quality, for prevention of risks of the health and environment, according to the agenda 21 and the model ISO 14001. This is a pilot project that we implemented and carry out with the participation of students, administrative officers and teachers of the Mining School. This serve as a small laboratory from which the most relevant variable was obtained gathered in order to works adequately the administrative system of pollution waste. We gathered 600 units of dry batteries and alkaline batteries this permitted to avoid the uncontrolled elimination of these pollutants to our environment, due to the great quantity of dangerous substances such as mercury, cadmium, manganese contained by these batteries. This situation makes necessary to realize an adequate management. We obtained a 50% with of mining school students. We also reached the help of the bachelors for this effort. As an added value we are changing habits and customs related to elimination of solid waste pollution residues.